The Validity of The Marriage Guardian in The Case of Elopement in The Perspective of Islamic Law - Fadilah Syafitra; Khosyi'ah, Sia (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2023)
The purpose of this study is to discuss the view of Islamic law on the validity of marriage guardians in cases of elopement. The research method used is a qualitative method with normative juridical. Data collection was carried out by observation and interview techniques for three elopement pairs and with the head of the local KUA. The results and discussion showed that the elopement factor occurred due to the parents' disapproval of the bride and groom's wedding plans. The disapproval was caused by financial unpreparedness and not being old enough for the bride and groom. The impacts caused are in the form of internal family problems, problems in state administration and social problems. The three elopement couples were married in the absence of a guardian who obtained guardianship permission from the guardianship of the nasab. In addition, marriages are performed without applying for marriage dispensation to religious courts because three of the six are minors. So it can be concluded that both religiously and legally in Indonesia, the marriage of the three couples is invalid.